TRANSLATING ISSUES OF ENGLISH RELIGIOUS TERMS - Abdullajonova Shakhnozakhon Qudratillo qizi; Sobirova Ranokhon Xakimovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article examines the challenges and complexities involved in translating English religious terms. Religious terminology often carries deep cultural and historical significance, making accurate translation crucial for effective communication and understanding across different languages and cultures. The article explores the various factors that contribute to the difficulties of translating religious terms, such as linguistic nuances, theological concepts, and cultural connotations. It also discusses different translation strategies employed by translators, including literal translation, adaptation, and cultural equivalence. The article highlights the importance of context and the need for a nuanced approach to translating religious terms, taking into account the target audience, cultural sensitivities, and the specific religious traditions involved.